2016
DOI: 10.3390/agronomy6020024
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of African-Bred Maize Germplasm Lines for Resistance to Aflatoxin Accumulation

Abstract: Abstract:Aflatoxins, produced by the fungus Aspergillus flavus, contaminate maize grain and threaten human food and feed safety. Plant resistance is considered the best strategy for reducing aflatoxin accumulation. Six maize germplasm lines, TZAR101-TZAR106, were released by the International Institute of Tropical Agriculture-Southern Regional Research Center (IITA-SRRC) maize breeding collaboration for use in African National Programs and U.S. maize breeding programs. The present investigation was conducted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 21 publications
4
28
0
Order By: Relevance
“…The estimation of resistance and stability of genotypes to AER, A. flavus colonisation, and aflatoxin accumulation was evaluated by an average environment coordination (AEC) method [15,16,28]. Stability of each genotype was explored by its projection onto the line drawn through the average environment and the biplot origin, the average environment axis (AEA; X-axis).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The estimation of resistance and stability of genotypes to AER, A. flavus colonisation, and aflatoxin accumulation was evaluated by an average environment coordination (AEC) method [15,16,28]. Stability of each genotype was explored by its projection onto the line drawn through the average environment and the biplot origin, the average environment axis (AEA; X-axis).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, line CKL05022 was an ideal genotype resistant to AER in Kiboko and Vaalharts. Several studies have identified such useful germplasm and recommended further testing of indifferent locations and environments to evaluate potential usefulness in breeding for resistance to aflatoxin accumulation [16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…General aflatoxin exposure can be reduced by improved field, harvesting, and storage practices, and by switching to crop hybrids less prone to aflatoxin contamination. Together with pre-and post-harvest strategies, and effective screening tools, host plant resistance is considered to be a practical and effective approach in reducing aflatoxin contamination in maize (Brown et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The resistant TZAR104 maize variety used in the current study is one of the six maize germplasm lines released by the International Institute of Tropical Agriculture-Southern Regional Research Center (IITA-SRRC) maize breeding collaboration for use in African National Programs and U.S. maize breeding programs (Menkir et al, 2006). TZAR104 was extracted from a backcross involving GT-MAS:gk (U.S. inbred line, with proven resistance to aflatoxin contamination) as a recurrent parent and KU1414-SR (tropical elite African inbred line with some level of resistance to aflatoxin production) as a non-recurrent parent (Brown et al, 2016). Therefore, the resistance exhibited by the TZAR104 kernels is a combination of resistant traits from both the U.S. and African lines to aflatoxin production and contamination based on direct resistance to diseases such as Aspergillus ear rot (Brown et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Considerable efforts have been made in identifying maize genotypes resistant to pre-harvest A. flavus infection and aflatoxin contamination (Brown et al 1995;Menkir et al 2006;Williams et al 2015). Several studies (Scott and Zummo 1988;Betrán et al 2006;Menkir et al 2008;Williams et al 2008;Brown et al 2016) have identified maize germplasm with high levels of resistance to aflatoxin accumulation over a range of environments. However, most of these resistant sources lack desirable agronomic performance and adaptation to target areas (Gorman et al 1992;Brown et al 1999;Brooks et al 2005;Warburton and Williams 2014).…”
Section: Introductionmentioning
confidence: 99%